Performance art en Chile : historia, procesos y discursos - González Castro, Francisco Alonso; López, Leonora; Smith, Brian (Ediciones Metales Pesados, 2016)
Book that explores the development of Performance Art in Chile between 1970 to 2000, trying to further some aspects of their practice throughout the 20th century and discussing the concepts of Performance and Performance art. The focus of the book is focused on practices, so its structure is from genealogies.